The impact of digitalization towards the Sustainability of Malaysian smes: The dynamic capabilities perspective - Abu Jaish, Anas Ahmad; Murdipi, Rafiqa; Abdul Razak, Dzuljastri; Mohd. Alwi, Norhayati (2022)
In many developing countries SMEs is considered as one of the main contributors to their economies. However, SMEs in Malaysia still face various challenges and issues in different sectors. Uncertainties such as Covid -19 and digitalization are the main current uncertain issues in Malaysia. This paper examines the resource capabilities of Malaysian SMEs in handling uncertain environments by identifying the importance of digitalization and humanization in their efforts to maintain the sustainability of their market. The quantitative method was employed by using a questionnaire to collect data that represented the research objective. A preliminary study is conducted to test the reliability and validity of the questionnaire. The paper also discusses the preliminary data analysis and descriptive analysis of study variables. As a result, the researcher addressed the preliminary study findings accordingly. The study found that SMEs somehow agreed that business sustainability depends on the speed of responses towards environmental changes, digitalization and humanization are considered the long-term sustainable business plan. This study contributes to the body of literature and benefits both governmental and non-governmental institutions, policymakers, and agencies by providing crucial information which assists them to identify the proper plan and assistance for SMEs. The greater concern will be on assisting the SMEs in being more stable and sustainable within the challenging uncertain market conditions.